Flexible employment: positive work strategies for the 21st century. - Lenz, Edward A. (Journal of Labor Research)
Part of a special section on flexible employment and alternative work arrangements. The writer argues that greater worker flexibility not only benefits businesses but offers individuals new pathways to permanent employment as well. Contrary to claims that businesses use flexible arrangements to avoid benefits or escape their legal obligations as employers, flexible work arrangements are used to supplement a business's permanent staff rather than replace it. Furthermore, the fact that flexible work arrangements are used to facilitate the movement of contingent workers into permanent positions negates the concern that workers become trapped in temporary and other contingent jobs. The need for changes in the current labor and employment laws and current tax rules relating to so-called leased employees are discussed.